Otitis media with effusion. Issue 4 (July 2015) - Atkinson, Helen; Wallis, Sebastian; Coatesworth, Andrew P
Abstract: Otitis media with effusion (OME) is a common problem facing general practitioners, pediatricians and otolaryngologists. This article reviews the etiopathogenesis, epidemiology, presentation, natural history and management of OME. The literature was reviewed by using the PubMed search engine and entering a combination of terms including 'otitis media with effusion', 'epidemiology' and 'management'. Relevant articles were identified and examined for content. What is the take home message? While OME is a very common entity in the pediatric population, the majority of cases will resolve spontaneously. Surgery in the form of grommet insertion, with or without adenoidectomy is the most effective treatment in persistent symptomatic cases.